Synthesis of gallic acid imprinted polymer and incorporation in poly(caprolactone) mat via electrospinning - J. D. P. Moraes Segundo; M. O. S. Moraes; W. R. Brito; K. Segala; Y. Garcia-Basabe; M. L. M. Rocco; M. A. d'Avila (eXPRESS Polymer Letters)
Molecularly imprinted polymers (MIP) are materials capable of recognizing specific molecules, usually through non-covalent bonds. In this work, gallic acid (GA) was selected as the imprinting molecule, and MIP for GA (MIP-GA) was synthesized by bulk polymerization. X-ray photoelectron spectroscopy (XPS) and near-edge X-ray absorption fine structure (NEXAFS) confirmed the MIP-GA recognition property. Poly(caprolactone) mat containing MIP-GA particles (MIM-GA) was produced by electrospinning, which was morphologically characterized by Scanning electron microscopy (SEM). Functionalized MIM-GA was obtained by washes sequence in methanol for the GA removal from MIM-GA. The GA removal was confirmed by High-performance liquid chromatography (HPLC) with UV-Vis detection at 214 and 268 nm. The functionalized MIM-GA immersed in GA methanolic solution with a concentration of 1.0 mM extracted 96±1.5% of GA at t =150 minutes. The vibrational modes obtained from FT-IR spectra confirmed the chemical composition of MIM-GA and its functionalization through of band at 770 cm–1. The contact angle measurements were 134.0±1.0° for electrospun MIM-GA and 125.0±1.2° for functionalized MIM-GA. The decrease was due to the absence of GA after the functionalization process. The produced MIM-GA by electrospinning acquired the recognition property of the GA imprinted polymer synthesized, which can be used for the specific detection, extraction, and purification of this important natural polyphenol.